Sports Clubs Can Contribute to the Physical Activity of Children and Adolescents in More Diverse and Sustainable Activities - Kokko, Sami; Ahokas, Ira; Leino, Henna; Lyytimäki, Jari; Raudasoja, Iina; Simula, Mikko; Tapio, Petri; Vasankari, Tommi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
An increasing number of children are taking part in supervised club activities, starting at a younger age. They also start focusing on one sport at a younger age, and the dropping out of club activities starts already at the age of 11. These changes are challenging the current club activities. There has been a large increase in participation in club activities. In the 1990s, just over 30% of children and young people in Finland practiced sports in a club, while today, the participation rate has risen to 60%. The age at which children start participating in club activities has decreased by an average of one year per decade. Those born before the 1950s typically started participating in clubs at the age of 12, compared with an average age of six today. This change means that children specialise in one sport and then drop out of club activities too early. As a result, the hobby does not continue as far into adolescence as it should. This increases the likelihood of inactivity in adolescence and further on in adulthood. The clubs do not need to fix the insufficient physical activity of the population alone, but they have the potential to develop their own activities in promoting physical activity and physical education, as well as their cooperation with other actors. This policy brief is the third and last in its series from the Healthy Lifestyles to Boost Sustainable Growth (STYLE) project, combining interdisciplinary knowledge on trends in transport and physical activity. Interpreting them through infrastructure and service designs and changing lifestyles, we generate insight on novel business opportunities and intervention models that induce physical activity. This provides innovative pathways towards current national policy targets and promotion of the societal vision. The project is funded by the Strategic Research Council at the Academy of Finland. Read more: www.styletutkimus.fi/en